Analisis Kebutuhan Guru pada Video sebagai Media Pembelajaran Kimia Berorientasi Proyek Terintegrasi Sustainable Development Issues untuk Materi Pemanasan Global dan Perubahan Iklim - Sari, Haslinda Nawang; Purtadi, Sukisman; Adila, Siti Nur (Universitas Negeri Surabaya, 2025)
Objective: This study aims to analyze the needs of high school chemistry teachers in developing project-oriented instructional videos integrated with Sustainable Development Issues (SDIs), especially in the context of teaching global warming and climate change. These topics are multidisciplinary and require not only conceptual understanding but also contextual application, aligning with the goals of the Merdeka Curriculum and 21st-century education. Method: This research employed a qualitative approach using an exploratory survey method. Data were collected through a semi-open questionnaire adapted from Rothwell et al. (2015), distributed to ten high school chemistry teachers in Yogyakarta. The data were analyzed thematically using two-stage coding to identify patterns and key themes from teacher responses. Results: The findings indicate that teachers have a strong understanding of the Merdeka Curriculum, learning media, instructional videos, SDGs, and project-based learning. However, challenges persist, especially in integrating SDGs and PjBL due to limited experience, lack of suitable video resources, and time constraints. Teachers expressed the need for chemistry learning videos with attractive visuals, contextual relevance, a duration of 6–10 minutes, and additional features such as quizzes and relatable illustrations. Novelty: This research highlights a specific gap in available educational resources by addressing the practical needs of teachers for effective video-based project learning tools integrated with sustainability issues. It provides a foundation for developing relevant, accessible, and pedagogically sound media to support chemistry education aligned with SDGs.